Microorganisms meet solid minerals: interactions and biotechnological applications - Kumar, Amit (2017)
In natural and engineered environments, microorganisms often co-exist and interact with various minerals or mineral-containing solids. Microorganism-mineral interactions contribute significantly to environmental processes, including biogeochemical cycles in natural ecosystems and biodeterioration of materials in engineered environments. In this mini-review, we provide a summary of several key mechanisms involved in microorganism-mineral interactions, including the following: (i) solid minerals serve as substrata for biofilm development; (ii) solid minerals serve as an electron source or sink for microbial respiration; (iii) solid minerals provide microorganisms with macro or micronutrients for cell growth; and (iv) (semi)conductive solid minerals serve as extracellular electron conduits facilitating cell-to-cell interactions. We also highlight recent developments in harnessing microbe-mineral interactions for biotechnological applications.